Deciphering the metabolic role of AMPK in cancer multi-drug resistance. (June 2019) - Tan, Wen; Zhong, Zhangfeng; Carney, Randy P.; Men, Yongfan; Li, Jiannan; Pan, Tingrui; Wang, Yitao
Abstract: Multi-drug resistance (MDR) is a curious bottleneck in cancer research and chemotherapy, whereby some cells rapidly adapt to the tumor microenvironment via a myriad of heterogeneous metabolic activities. Despite being a major impediment to treatment, there is a silver lining: control over metabolic regulation could be an effective approach to overcome or correct resistance pathways. In this critical review, we comprehensively and carefully curated and analyzed large networks of previously identified proteins associated with metabolic adaptation in MDR. We employed data and text mining to study and categorize more than 600 studies in PubMed, with particular focus on AMPK, a central and fundamental modulator in the energy metabolism network that has been specifically implicated in cancer MDR pathways. We have identified one protein set of metabolic adaptations with 137 members closely related to cancer MDR processes, and a second protein set with 165 members derived from AMPK-based networks, with 28 proteins found at the intersection between the two sets. Furthermore, according to genomics analysis of the cancer genome atlas (TCGA) provisional data, the highest alteration frequency (80.0%) of the genes encoding the intersected proteins (28 proteins), ranked three cancer types with quite remarkable significance across 166 studies. The hierarchical relationships of the entire identified gene and protein networks indicate broad correlations in AMPK-mediated metabolic regulation pathways, which we use decipher and depict the metabolic roles of AMPK and demonstrate the potential of metabolic control for therapeutic intervention in MDR.